Polyethyleneimine/polyethylene glycol–conjugated gold nanoparticles as nanoscale positive/negative controls in nanotoxicology: testing in frog embryo teratogenesis assay–Xenopus and mammalian tissue culture system. Issue 1 (2nd January 2023) - Hwang, Yoo-Seok; So, Daeho; Lee, Moonsup; Yoon, Jaeho; Reipa, Vytas; Tona, Alessandro; Yi, Feng; Nelson, Bryant C.; LaVan, David A.; Hackley, Vincent A.; Daar, Ira O.; Cho, Tae Joon
Abstract: Despite the great potential of using positively charged gold nanoparticles (AuNPs) in nanomedicine, no systematic studies have been reported on their synthesis optimization or colloidal stability under physiological conditions until a group at the National Institute of Standards and Technology recently succeeded in producing remarkably stable polyethyleneimine (PEI)-coated AuNPs (Au-PEI). This improved version of Au-PEI (Au-PEI25kB) has increased the demand for toxicity and teratogenicity information for applications in nanomedicine and nanotoxicology. In vitro assays for Au-PEI25kB in various cell lines showed substantial active cytotoxicity. For advanced toxicity research, the frog embryo teratogenesis assay– Xenopus (FETAX) method was employed in this study. We observed that positively-charged Au-PEI25kB exhibited significant toxicity and teratogenicity, whereas polyethylene glycol conjugated AuNPs (Au-PEG) used as comparable negative controls did not. There is a characteristic avidity of Au-PEI25kB for the jelly coat, the chorionic envelope (also known as vitelline membrane) and the cytoplasmic membrane, as well as a barrier effect of the chorionic envelope observed with Au-PEG. To circumvent these characteristics, an injection-mediated FETAX approach was utilized. Like treatment with the FETAX method, the injection of Au-PEI25kB severely impaired embryo development. Notably, the survival/concentration curve that was steep when the standard FETAX approach was employed became gradual in the injection-mediated FETAX. These results suggest that Au-PEI25kB may be a good candidate as a nanoscale positive control material for nanoparticle analysis in toxicology and teratology.